INTERPRETATION OF POETRY THE CHARGE OF THE LIGHT BRIGADE BY ALFRED, LORD TENNYSON - Wandana, Muhammad Ridho (TRANSFORM: Journal of English Language Teaching and Learning, 2020)
This study discusses indirect descriptive expressions in the poem The Charge of the Light Brigade by Alfred, Lord Tennyson use semiotics theory of Riffaterre. This study aims to, (a) describe the kinds of indirect descriptive expressions used in the poetry The Charge of the Light Brigade by Alfred, Lord Tennyson, (b) explain the realization of indirect descriptive expressions realized in the poetry The Charge of the Light Brigade by Alfred, Lord Tennyson, (c) explain the reasons of indirect descriptive expressions realized in the ways they are. This research is a qualitative descriptive study. The data source used in this study is in the form of words, phrases, clauses and sentences from the poem. The results of this study, namely there are 8 Metaphors and 7 Metonymy in displacing of meaning; 6 Ambiguous, 2 Contradictions, and 4 Nonsense in distorting of meaning; 16 rhymes, 12 enjambments, and 6 typography in creating of meaning.